The dangers of mental health promotion in schools - Timimi, Sami; Timimi, Zoe (Journal of Philosophy of Education, 2022)
Much of Western media has promoted the idea that we are facing an epidemic of mental illness and psychiatric emergencies in contemporary Western society and worldwide, and that young people are a particularly vulnerable group. Schools have become a prominent site of concern and focus for this discourse as mental health problems are said to start early in life; thus, targeting intervention at people in their early years and greater mental health awareness amongst staff and pupils are perceived as important mental disorder prevention strategies. However, the belief that mental disorders can be classified and investigated using the same tools as physical health has led to a system of knowledge that lacks validity being constructed. This ideology, far from leading to enlightened progress that will prevent and/or ameliorate future mental health problems, inadvertently sets young people on a path towards alienation from, and suspicion of, their emotional lives and a lack of curiosity about, or tolerance of, suffering. This article explores how a lack of understanding about what sort of ‘thing’ a mental health problem/disorder/diagnosis/illness is leads to confusion about the meaning and consequences of experiencing mental distress and/or mental difference. Interviews with secondary school teachers carried out by one of the authors (ZT) show how awareness of mental health and mental disorder has increased in UK secondary schools over the last decade and how this has led to an expansion in the numbers of students thought to have mental health problems that required professional intervention. As a result, teachers now identify many behaviours and experiences they previously deemed ordinary and/or understandable as likely mental health problems that required professional expertise they lacked. Rather than preventing mental health problems, it is likely that this ideology, and the resulting practices it encourages, are creating them.
Keywords: critique; diagnosis; mental health; schools; young people